ETHNOPHARMACOLOGICAL SURVEY OF THE MEDICINAL PLANTS USED IN TINDIRET, NANDI COUNTY, KENYA - Kigen, Gabriel; Maritim, Alice; Some, Fatuma; Kibosia, John; Rono, Hillary; Chepkwony, Simon; Kipkore, Wilson; Wanjoh, Bernard (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: An inventory of the medicinal plants used by herbalists to treat various ailments in Tindiret area of Nandi County, Kenyawas conducted by a team comprising of medical researchers and botanists with a view to preserve indigenous ethnobotanical knowledgeand potential research and development of new drugs.Materials and Methods: Data was collected from practicing herbalists through semi-structured interviews, group discussions andobservations. The types of medical conditions treated, treatment methods as well as the plants used were recorded.Results and Conclusion: A total of 50 medicinal plants belonging to 28 families used for the treatment of 32 medical conditions wererecorded. The disease conditions which were treated by the highest number of plants were abdominal/colic pains with 15 different plantsrecorded (13%), respiratory disorders 15(13%) and infertility14 (12%). The most widely used medicinal plants were Vernoniaamygdalina 7(7%), Toddalia asiatica 6(6%), Aloe kedongensis 5(5%) and Zanthoxylum gilletii 5(5%); whereas the families with thehighest number of plant usage were Fabaceae 8(14%), Lamiaceae 4(8%) and Solanaceae 4(8%) plants respectively. The studydocuments important ethno-medical knowledge on the plants used by herbalists in Tindiret sub-county.